Reduction of Cogging Torque by Adapting Bifurcated Stator Slots and Minimization Of Harmonics And Torque Ripple in Brushless DC Motor - M. Arun Noyal Doss; K. Mohanraj; V. Kalyanasundaram; K. Karthik (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper proposes an improved methodology to minimize the cogging torque, harmonics and torque ripples in Brushless DC (BLDC) motor. The cogging torque is reduced by designing the BLDC motor with bifurcated active surface area using Finite Element Analysis (FEA). The harmonics and torque ripple is minimized using PI and Fuzzy controllers. These controllers are analyzed to bring out an optimal solution. The effectiveness and flexibility of the individual techniques of proposed control method is verified through simulations [Matlab Simulink]. The experimental result is shown only for fuzzy control because fuzzy is better comparing the performance of PI controllers.